Solve for y y

Algebra Level 3

y a c = x b c = z a b \dfrac{ y}{a-c} = \dfrac x{b-c} = \dfrac z{a-b}

Find the value of y y in terms of a a , b b , c c , x x and/or z z .

a + b a+b a b a-b x z x-z x + z x+z

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Let :-
y a c = x b c = z a b = k \implies \dfrac{ y}{a-c} = \dfrac x{b-c} = \dfrac z{a-b}=k

y = k a k c . . . ( 1 ) y=ka-kc \ \ \ ...(1)

x = k b k c . . . ( 2 ) x=kb-kc \ \ \ ...(2)

z = k a k b . . . ( 3 ) z=ka-kb \ \ \ ...(3)

( 1 ) ( 2 ) ( 3 ) \implies (1)-(2)-(3)

y = x + z y=\boxed{x+z}

Mounika Myla
Sep 12, 2016

x=y b c a c \frac{b-c}{a-c} = y b y c a c \frac{yb-yc}{a-c} z=y a b a c \frac{a-b}{a-c} = y a y b a c \frac{ya-yb}{a-c} x+z= y ( a c ) a c \frac{y(a-c)}{a-c} x+z=y

Can you explain how x = y b c a c x = y \dfrac{b-c}{a-c} ?

y b x = x a c x = y a c b c \dfrac{y}{b-x} = \dfrac{x}{a-c} \\ \implies x = y\dfrac{a-c}{b-c} ?

Viki Zeta - 4 years, 9 months ago
Rab Gani
May 25, 2018

let a – c =p, b – c =q, a – b = r, then p = q + r, y/p = x/q = z/r = k, then y=kp, x=kq, z=kr. So y=x+z

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...